Genomic insights into host-associated variants and transmission features of a ToBRFV isolate from Mexico - Zamora-Macorra, Erika Janet; Ochoa-Martínez, Daniel Leobardo; Chavarín-Camacho, Claudia Yaritza; Hammond, Rosemarie W.; Aviña-Padilla, Katia (Frontiers in Plant Science, 2025)
Tomato brown rugose fruit virus (ToBRFV) poses a global threat to tomato and pepper production due to its high transmissibility and adaptability. Understanding its genomic features and transmission mechanisms is critical for effective disease management. We characterized the genome and biological properties of a ToBRFV isolate from Mexico. Comparative genomic analyses were conducted using 100 global genomes, with particular focus on single nucleotide variants (SNVs) and their distribution across different host species. Phylogenetic analysis and experimental bioassays, including seed transmission tests, were also performed. Phylogenetic analysis revealed genetic proximity between the Mexican isolate and strains from Mexico, USA, Canada, Israel, and China, indicating shared transmission routes. Genomic comparisons confirmed general sequence stability, but SNVs were found in the 126-kDa replicase, particularly within the methyltransferase domain. These SNVs exhibited host-associated patterns, with conserved profiles in tomato and unique substitutions in Capsicum annum, Solanum nigrum, and Citrullus lanatus. Bioassays demonstrated susceptibility in additional solanaceous hosts, and seed transmission assays in Nicotiana rustica indicated reduced germination and low-frequency viral detection in seedlings. The study highlights the genomic conservation and host-specific variation in ToBRFV, suggesting that the methyltransferase domain may undergo differential evolutionary pressures. The findings provide valuable insights for improving risk assessment, seed health testing, and biosecurity measures.